Typification of the name Iris sanguinea (Iridaceae) - Boltenkov, Eugeny V. (Phytotaxa, 2018)
The genus Iris Linnaeus (1753: 38), when considered in a wide sense (Mathew 1989, Goldblatt et al. 2008), was established with a total of eighteen species. Presently, it comprises approximately 225 species (Goldblatt et al. 1998), distributed mostly in temperate regions of the Northern Hemisphere.